Application and Algorithm Analysis of Micro-Expression Recognition. (August 2020) - Cai, Zhaoqi; Yan, Shaowen
Abstract: Micro-expressions (MEs) are the expressions of real emotion in people's heart. It usually happens when people want to hide their true emotions. Through the study of MEs, we can correctly speculate on the inner activities of the expressors, which has important application value in the fields of criminal investigation, arrest, psychotherapy, education and teaching. At present, more and more people are paying attention to the research of ME recognition. People try to detect MEs by faster algorithms, but the recognition process is affected by many factors, so it is necessary to optimize related technologies as soon as possible to achieve higher accuracy. Therefore, this paper analyzes the application of ME recognition and related algorithms, and puts forward the development prospects.